2012
DOI: 10.1017/s1751731112000341
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping strategies for genomic selection in small dairy cattle populations

Abstract: This study evaluated different female-selective genotyping strategies to increase the predictive accuracy of genomic breeding values (GBVs) in populations that have a limited number of sires with a large number of progeny. A simulated dairy population was utilized to address the aims of the study. The following selection strategies were used: random selection, two-tailed selection by yield deviations, two-tailed selection by breeding value, top yield deviation selection and top breeding value selection. For co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 32 publications
9
35
1
Order By: Relevance
“…In fact, our results suggest that when resources are limited to compose a training dataset, the best approach may be to genotype only the animals with high EBV. Some simulation studies show that selecting only the top animals may lead to substantially biased [31] and inaccurate predictions [32]. In our study, reliabilities for four out of six traits were higher for the TOP50 scenario than for the RAN50 scenario.…”
Section: Discussionmentioning
confidence: 46%
“…In fact, our results suggest that when resources are limited to compose a training dataset, the best approach may be to genotype only the animals with high EBV. Some simulation studies show that selecting only the top animals may lead to substantially biased [31] and inaccurate predictions [32]. In our study, reliabilities for four out of six traits were higher for the TOP50 scenario than for the RAN50 scenario.…”
Section: Discussionmentioning
confidence: 46%
“…The limited number of phenotypic records for feed intake will, however, result in a relatively low accuracy of genomic selection for feed intake. One solution to partly overcome this effect of the limited size of the reference population is to optimize its design (Jimé nez-Montero et al, 2012, Pszczola et al, 2012a. Another solution, commonly used in traditional breeding programmes, is to use predictor traits.…”
Section: Introductionmentioning
confidence: 99%
“…With ~10,000 bulls in the training population, accuracies of the GEBV of young bulls without daughter records approach those of EBV obtained with progeny tests with ~50 daughters per sire, (Lund et al, 2011;Wiggans et al, 2011), whereas accuracies of GEBV for young bulls derived from reference populations of ~1,000 genotyped bulls are generally no higher than traditional BLUP based only on pedigree information (Thomasen et al, 2012;Van Grevenhof et al, 2012). Jiménez-Montero et al (2012) suggested that more accurate GEBV could be obtained with training populations consisting chiefly of genotyped cows with EBV computed based on their own records. The potential number of genotyped cows with records is much larger than the number of bulls with progeny tests.…”
Section: Introductionmentioning
confidence: 89%